Particle swarm optimisation algorithm for non-linear camera calibration. (1st January 2012) - Zhang, Jian-de; Lu, Jin-gui; Li, Hong-liang; Xie, Min
Particle swarm optimisation algorithm (PSO) is applied to solve the difficult optimisation problem of camera calibration in this paper. The model of camera calibration is discussed. An accumulation factor related to the iteration number of PSO is given for the optimisation problem of camera calibration, and the computer implementation procedure is discussed for the application of particle swarm optimisation algorithm in optimisation problem of camera calibration in this paper. Numerical experiments have been performed to evaluate the efficiency of PSO for optimisation problem of camera calibration.